Investigation of Structure and Optical Properties for Copper Oxide Thin Films on Plastic Substrate by Helicon Plasma DC Magnetron Sputtering Technique - Anmar Alhattab; Haider Alhattab; Ichiro Takano (Advances in Materials Science and Engineering)
As we move towards a decarbonized society, transparent solar cells have recently become an important means of increasing power generation in familiar locations. Copper oxide has been attracting attention as a candidate material for the production of transparent solar cells. In order to further expand the range of applications, it is believed that it will be necessary to develop flexible, transparent plastic substrates. For the purpose of optical applications, copper oxide thin films with CuO, Cu2O, or both phases were fabricated on highly transparent plastics such as poly-methyl methacrylate (PMMA) and polycarbonate (PC), as well as on a glass substrate as a comparable sample. The helicon plasma DC magnetron sputtering method was used to fabricate thin films at a low deposition temperature due to the low heat resistance of plastic substrates. In addition, the helicon plasma DC magnetron sputtering method is capable of depositing films at low vacuum pressure, which enables the preparation of thin films with high crystallinity. The structure, surface shape, and optical properties of fabricated films were investigated using X-ray diffraction (XRD), a laser microscope, and a UV-Vis spectrophotometer, respectively. In this study, the formation of copper oxide thin films on plastic substrates at low temperatures has been verified, as have the crystal structure and optical properties, which is considered a rare study in this field.